2022
DOI: 10.1098/rsob.220216
|View full text |Cite
|
Sign up to set email alerts
|

Cell quiescence in planarian stem cells, interplay between p53 and nutritional stimuli

Abstract: Cell quiescence appeared early in evolution as an adaptive response to adverse conditions (i.e. nutrient depletion). In metazoans, quiescence has been involved in additional processes like tissue homeostasis, which is made possible by the presence of adult stem cells (ASCs). Cell cycle control machinery is a common hub for quiescence entrance, and evidence indicates a role for p53 in establishing the quiescent state of undamaged cells. Mechanisms responsible for waking up quiescent cells remain elusive, and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…In our previous paper, we demonstrated that the interplay between p53 and nutritional stimuli regulates planarian stem cell quiescence [23] and additional literature data support that the ancestral activity for which p53 was selected for, is related to stem cell biology [24–27]. This is also true for planarian in which Smed‐p53 is not involved in the response to genotoxic stress [28].…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…In our previous paper, we demonstrated that the interplay between p53 and nutritional stimuli regulates planarian stem cell quiescence [23] and additional literature data support that the ancestral activity for which p53 was selected for, is related to stem cell biology [24–27]. This is also true for planarian in which Smed‐p53 is not involved in the response to genotoxic stress [28].…”
Section: Resultsmentioning
confidence: 88%
“…A special mention should be dedicated to Djp53 , which in D. japonica is enriched in the stem cell compartment [23]. Djp53 is an antiproliferative factor [23] and its downregulation in a fasting regimen might be consistent with the ability of planarians to maintain a constant bmi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations